PERBANDINGAN PERLINDUNGAN HUKUM TENAGA KERJA PEREMPUAN DI INDONESIA DAN SINGAPURA - Febri Jaya; Andy Sanjaya (UNIB Press, 2022)
The writing and preparation of this article was carried out with the aim of discussing and implementing legislation for women workers in Indonesia and Singapore in terms of rights for women workers as well as negotiations for companies that do not give rights to women workers. Then with this thesis it is expected to be able to provide additional material and insight about the law in work agreements for students and women workers. This type of research is normative legal research through secondary data collection and primary data. Secondary data collection agreed upon data collection through literature study / literature review. Then researchers use qualitative data analysis methods through data collection from personal or official documents, writing the source of this information can draw conclusions from the research conducted. The results of this study indicate that there are similarities and differences in the implementation of the protection of the rights of women workers in Indonesia and Singapore, but both countries highly respect the rights of women workers in their respective countries.